The spectrum of women's health care in Latin America. (7th August 2018) - Wilkinson, Jeffrey; Papageorghiou, Aris; Witkin, Steven S; Thorp, John
Abstract : Scientific Editor, Dr Jeffrey Wilkinson, discusses his top articles from this issue in an audio podcast available at:https://soundcloud.com/bjog/september-editors-choice-2018